President's Message - Mushayandebvu, Barbara (Operating Room Nurses Association of Canada Journal, 2019)
Professionalism in nursing means different things to different people. Some define professionalism as a nurse’s knowledge, skill-set and how care is delivered to patients. Others view professionalism as the continuous journey to improve nursing practices, the workplace, and nursing’s future. RNAO defines it as “Qualities or typical features of a profession or professional. A collection of attitudes and actions; it suggests knowledge and technical skill.”1